2016
DOI: 10.1210/jc.2015-3891
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Leptin Administration on Circulating Apolipoprotein CIII levels in Patients With Lipodystrophy

Abstract: Leptin replacement in lipodystrophy did not alter serum apoCIII levels. Elevated apoCIII may play a role in the hypertriglyceridemia of lipodystrophy independent of leptin deficiency and replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Plasma concentrations of apoC-III were previously found to be associated with the degree of insulin resistance as estimated by HOMA (38). ApoC-III inhibition may also enhance the sensitivity to the normal insulin-mediated suppression of APOC3 gene expression (10), which is dysregulated in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma concentrations of apoC-III were previously found to be associated with the degree of insulin resistance as estimated by HOMA (38). ApoC-III inhibition may also enhance the sensitivity to the normal insulin-mediated suppression of APOC3 gene expression (10), which is dysregulated in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that elevated apoC-III is associated with the hypertriglyceridemia seen in both generalized and partial lipodystrophy, suggesting that apoC-III may represent a therapeutic target in these patients (38). Patients with lipodystrophy, unable to store excess calories in adipocytes, develop ectopic lipid deposits in muscle and liver, which lead to an increase flux of free fatty acids and severe insulin resistance (39).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies -NCT02639286 (data unpublished yet) and NCT02527343 [71] -have supported the role of antisense oligonucleotide anti-APOC3 in patients with partial lipodystrophy. Leptin replacement may decrease ApoC-III by reducing plasma fasting glucose levels, as it has been demonstrated in leptin deficient ob/ob mice [68], but in humans, it is not enough to manage the metabolic complications of lipodystrophy, in particular hypertriglyceridemia [70]. For this reason, ApoC-III inhibitors may represent a valuable therapeutic option in the future for treatment of lipodystrophy.…”
Section: Apoc-iii: Obesity and Lipodystrophymentioning
confidence: 99%
“…Metreleptin may disrupt events that lead to lipotoxicity, as improvements in hepatic and intramyocellular lipid content, liver volume and steatohepatitis have occurred with the drug in LD patients [5,9]. Elevated levels of apolipoprotein CII and ANGPTL3 (proteins that inhibit lipoprotein lipase) in patients with LD may contribute to hypertriglyceridaemia, with levels of ANGPTL3 (but not apolipoprotein CII) being reduced by metreleptin [16,17]. Reductions in plasma levels of PCSK9 (a protein that promotes hypercholesterolaemia) have also been seen with metreleptin in LD patients, with a decline in creatinine clearance (likely indicating reduced glomerular hyperfiltration) [24].…”
Section: How Does Metreleptin Work?mentioning
confidence: 99%